Conservative treatment of intact ectopic pregnancy with methotrexate (Research, Society and Development, 2022)
Introduction: Ectopic pregnancy (EP) is generally defined as the implantation of the blastocyst outside the uterine cavity, synonymous with extrauterine pregnancy. Objective: To analyze the effectiveness of conservative treatment with methotrexate (MTX) in intact EP. Methods: This is a systematic review carried out through extensive research in the medical literature using the electronic databases: Medline (PubMed) and LILACS, with the following search strategy: ("Pregnancy, Ectopic"[Majr] AND "Drug Therapy "[Mesh]). Results: The selected studies converge to demonstrate the effectiveness of conservative treatment with MTX in intact EP and were grouped into three main groups: Patients undergoing conservative treatment with MTX in the single-dose (SD) protocol, patients undergoing the double-dose (DD) protocol and patients undergoing conservative treatment who do not meet the protocol criteria for the use of MTX. The results showed that the MTX SD protocol has sufficient efficacy in the treatment of EP, but in patients outside the parameters required by the current protocol, treatment success increases with the use of the DD or multiple dose method. Conclusions: The SD protocol with the option to elaborate for a second dose in case of treatment failure may be the ideal treatment for intact EP.